2023
DOI: 10.1002/joa3.12911
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of morbidity and in‐hospital mortality following procedure‐related cardiac tamponade

Saurabh Deshpande,
Hiroyuki Swatari,
Raheel Ahmed
et al.

Abstract: BackgroundCardiac tamponade (CT) can be a complication following invasive cardiac procedures. We assessed CT following common cardiac electrophysiology (EP) procedures to facilitate risk prediction of associated morbidity and in‐hospital mortality.MethodsPatients who underwent various EP procedures in the cardiac catheterization lab (ablations and device implantations) were identified using the International Classification of Diseases, Ninth and Tenth Edition, Clinical Modification (ICD‐9‐CM and ICD‐10‐CM, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…An intriguing observation made in their study is the comparatively higher incidence of cardiac tamponade after catheter ablation, approximately 5%, 1 as contrasted with a lower incidence, below 1%, reported in the Japanese context. 2 It would be insightful for the authors to conduct a comparative analysis between countries, delving into the incidence of procedure‐related complications, including cardiac tamponade.…”
mentioning
confidence: 70%
See 2 more Smart Citations
“…An intriguing observation made in their study is the comparatively higher incidence of cardiac tamponade after catheter ablation, approximately 5%, 1 as contrasted with a lower incidence, below 1%, reported in the Japanese context. 2 It would be insightful for the authors to conduct a comparative analysis between countries, delving into the incidence of procedure‐related complications, including cardiac tamponade.…”
mentioning
confidence: 70%
“…Deshpande and colleagues conducted a rigorous investigation into the incidence of cardiac tamponade following invasive cardiac procedures, utilizing a nationwide inpatient sample database. 1 Their compelling findings demonstrated that the occurrence of cardiac tamponade during cardiac electrophysiology procedures ranged from 3.4% to 7.0%, with a corresponding in‐hospital mortality rate of 2.2% in real‐world clinical settings. However, several pertinent concerns have been raised regarding the scope of their study.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Also, all these patients underwent pericardiocentesis, a few requiring other surgical interventions and transfusion as well, as has been mentioned in our supplementary file and our methods section. 3 We have divided these complications into two types of events—intervention‐related events (viz. hemopericardium, acute post‐hemorrhagic anemia, hemorrhage complicating a procedure, or hematoma) or severe events (viz.…”
mentioning
confidence: 99%
“…To find out the modifiable predictors for the events (especially mortality), we carried out a multivariable logistic regression analysis including patient comorbidities and hospital bed size (wide methods section), which did not reveal any statistically significant factor. 3 …”
mentioning
confidence: 99%